Civil Society Organisations and Democratic Consolidation in Uganda - Katusiimeh, Mesharch W. (African Journal of International Affairs, 2004)
consolidation in Uganda. It argues that civil society organisations (CSOs) play an important role in building democratic governments but also questions whether the CSOs can live up to the theoretical expectations of building democratic governments. This paper, based on case study evidence from Uganda, attempts to bridge the gap between theory and reality by offering a realistic assessment of CSOs’ capabilities as regards democratic consolidation. Because of Uganda’s political history, political activism and political advocacy have not been widely embraced by CSOs. Negative political experiences have created some apathy and wariness resulting in many CSOs maintaining that they are apolitical. As a result, CSOs havefailed to mark distance from the NRM government in a manner that affirms their autonomous and independent growth. Ultimately, such a posture has undermined the CSOs’ cause and has confined them to issues that do not fundamentally challenge or affect the status quo.